Benefits of Sago pulp as litter material and its effect on the broilers performance. (March 2019) - Soplanit, S; Musa, Y; Arsyad, M; Darma, R; Syaiful, S A; Herdjiono, M V I; Hasnah,; Hakim, MR
Abstract: The study was aimed to determine the best combination of sago pulp and rice husk as litter material and its effect on the broiler performance including body weight, feed consumption, feed conversion ratio, and mortality rate. A totoal of 96 chicks were randomly assigned according to the Completely Randomized Design (CRD) with 4 treatments and 3 replications, and each replication consisting of 8 broilers. The treatments applied were litter with a combination of 0% Sago Pulp (SP) + 100% RH (Rice Husk); 25% SP + 75% RH; 50% SP + 50% RH; 75% SP + 25% RH, respectively. The measured parameters were weekly body weight, body weight gain, feed consumption, feed conversion ratio. The results showed that combination of SP and RH as litter material affect significantly weekly body weight gain, feed consumption, feed conversion ratio. The final body weight of chicken was highest on combination of 75%SP+25%RH (2316.67 g/bird), the highest feed consumption on combination of 0%SP+100%RH (2319 g/bird) and the lowest on 50%SP+50%RH (2298.5 g/bird), the most efficient feed convertion ratio on combination of 75%SP+25%RH (1.11). The results indicated that the best chicken performance was obtained from combination of 75%SP+25%RH as litter materials.